Women leaders in the Student Christian Movement, 1880-1920 - Russell, Thomas Arthur (American Society of Missiology series, 2017)
The SCM -- The "whys" of SCM's women leaders -- SCM committee women -- SCM general and assistant general secretaries -- Introducing the traveling secretary -- The ministry of the traveling secretary -- SCM short and long term pioneers -- SCM targeted student group pioneers -- Scm "warp and woof" pioneers -- SCM conference speakers -- SCM ecumenical pioneers -- SCM intellectual pioneers (biblical criticism and the social sciences) -- SCM social gospel pioneers -- SCM woman's movement pioneers (definition and causes) -- SCM woman's movement pioneers (benefits) -- Final thoughts